2019
DOI: 10.1002/micr.30539
|View full text |Cite
|
Sign up to set email alerts
|

The use of lower abdominal perforator flaps in soft‐tissue reconstruction after sarcoma resection

Abstract: Background Historically, conventional musculocutaneous flaps have been commonly used for reconstruction after soft tissue sarcoma resection, and the use of lower abdominal perforator flaps has not been popular. This report examined the current role of lower abdominal perforator flaps in sarcoma treatment. Methods We reviewed the outcomes of 14 patients (mean age: 46.3 years, range: 18–79 years) who underwent immediate reconstruction with a deep inferior epigastric artery perforator (DIEP) flap or a superficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The authors found that in most cases, a pedicled flap was used, with the ALT flap being the most common. Our literature review found four other case reports or case series (47,48,117,119). All cases utilized the DIEP flap in pedicled fashion.…”
Section: Groin Reconstructionmentioning
confidence: 98%
See 1 more Smart Citation
“…The authors found that in most cases, a pedicled flap was used, with the ALT flap being the most common. Our literature review found four other case reports or case series (47,48,117,119). All cases utilized the DIEP flap in pedicled fashion.…”
Section: Groin Reconstructionmentioning
confidence: 98%
“…All were reconstruction cases after sarcoma resection (41)(42)(43)(44)(45)48). All authors used the DIEP flap in pedicled fashion (41,43,(47)(48)(49) except Bota et al (42), who described raising an abdominoplasty-like paddle and transferred it as a free flap. Scaglioni et al (41).…”
Section: Hip and Thigh Reconstructionmentioning
confidence: 99%
“…Response to letter commenting on "The use of lower abdominal perforator flaps in soft-tissue reconstruction after sarcoma resection" We thank Dr. Giunta et al for their comments on our article, "The use of lower abdominal perforator flaps in soft-tissue reconstruction after sarcoma resection," (Miyamoto, Arikawa, & Kagaya, 2020) and for reporting their experience with a pedicled transverse deep inferior epigastric artery perforator (DIEP) flap (Giunta, De Brucker, & Hamdi, 2020).…”
mentioning
confidence: 99%
“…Distal circulation of the DIEP flap is more stable with the oblique design, and the flap can be safely harvested to the mid-axillary line. (Miyamoto et al, 2020). A 51-year-old woman presented with a recurrent angiosarcoma on her back.…”
mentioning
confidence: 99%
“…We read with interest the article by Miyamoto, Arikawa, and Kagaya regarding the use of lower abdominal perforator flaps in reconstruction after sarcoma resection (Miyamoto, Arikawa, & Kagaya, 2020).…”
mentioning
confidence: 99%